USING GMOS IN FOOD PRODUCTION - Begaliev Abdikayum (Лучшие интеллектуальные исследования, 2024)
Аbstract: This article summarizes the results of laboratory studies conducted in animals on the effects of genetically modified products by many scientists, and on this basis provides opinions and comments on the pros and cons of genetic modification. It was also noted that a large-scale study should be conducted in this regard in our country.